In the Modern Theory of Construction of Econometic Models of Development of Agricultural Production - Jabborov Elbek Erkin o’g’li (Research Parks Publishers, 2022)
The theoretical foundations of the mechanisms for building and forecasting an empirical model using systematic analysis and digital technologies have been improved to ensure macroeconomic sustainability of agricultural production development. Effective use of basic production resources, or in general, the level of utilization of existing potential in ensuring macroeconomic sustainability of agricultural production development is assessed.